Shell accumulation on seabed due to suspended coastal oyster farming and effects on burrowing capacity of the polychaete Perinereis aibuhitensis - Cao, Yujie; Shi, Rongjun; Han, Tingting; Liu, Huaxue; Huang, Honghui; Qi, Zhanhui (Frontiers in Marine Science, 2023)
Mariculture of bivalves releases shell debris that can accumulate on the seabed under farms. The ecological consequences of shell accumulation on the bioturbation of benthic macrofauna are not yet fully understood. Thus, it is necessary to quantify the shell debris that accumulated under bivalves farms and evaluate whether the shell debris hinders the burrowing capacity of macrofauna. However, no data are available on shell accumulation due to oyster farming and its possible effects on the burrowing capacity of polychaetes. Thus, we conducted a preliminary study on shells debris accumulation under an oyster farm in Daya Bay, southern China, and assessed the effects of shell accumulation on the burrowing activity of the polychaete Perinereis aibuhitensis in a mesocosm experiment. The results showed that oyster farming significantly (p < 0.05) increased the accumulation of shell debris under the farm. The amount of shell debris under oyster farm (6.0 1.3 kg (dry weight (DW)) m-2 or 130.0 24.7 g (DW) kg-1 dry sediment) was approximately two times that in a non-culture area (3.5 0.9 kg (DW) m-2 or 74.9 10.5 g (DW) kg-1 dry sediment). The presence of shell debris did not affect the survival of P. aibuhitensis in experiment, but the animals in sediment with shell added exhibited greater losses of body weight compared with those without. The numbers of burrowing holes were lower in sediment with shell debris added compared with those in sediment without shell addition throughout the experiment. Whereas, this does not due to the P. aibuhitensis in +Shell treatment were less active in terms of their burrowing activities. The lower numbers of holes in +Shell treatment was mainly due to P. aibuhitensis were unable to use surface areas where shells were present, the amount of area occupied by shell material physically prevented P. aibuhitensis from forming burrows in these locations. The hindering effects of shells on the burrowing activity of P. aibuhitensis would decreased as the shells degraded into debris. Therefore, we recommend using small shells when conducting “shell addition” bioremediation strategies to avoid the possible negative effects of shells on burrowing by polychaetes.